PENGGUNAAN GULA PASIR LOKAL SEBAGAI PLASTICIZER PADA ADUKAN MORTAR UNTUK PEMBUATAN CONBLOCK - Rifany K., Dian; Satyarno, Iman; Tjokrodimuljo, Kardiyono (Civil Engineering Forum Teknik Sipil, 2008)
Cement mortar (cement, sand and water mixture) has been widely applied as building materials, such as cement plaster, conblock, concrete brick, roof tile, etc. To obtain good quality conblock, one of the efforts is by adding cane sugar the plasticizer into a mortar mixture. Although cane sugar addition can reduce the use of cement and water, but the mortar workability degree can still be maintained. Reduction of the cement used also reduces the cost needed to make the cement mortar, which produces a more economical conblock. The objective of this research is to identify the cement ratio, specific gravity, compressive strength, water absorption, and endurance of the conblock through the abrasion test. This research was carried out in the Construction Material Laboratory of Civil and Environmental Engineering Department of Gadjah Mada University. Conblocks used as samples were ones produced by Diamond Baru Conblock Baru Yogyakarta. The materials for producing material consisted of Portland cement Type I produced by Gresik cement factory, and sand from Krasak River in Yogyakarta. The local cane sugar used was produced by Madukismo Sugar Factory in Yogyakarta. The mixture samples were made using cement-sand at various ratios of 1:2, 1:4 and 1:6. For each ratio, two types of samples were made and one of them was added with cane sugar at 2% of the cement weight. Twenty samples of conblock specimens were made for each variation, both for with and without cane sugar addition. The conblock dimension was 200 x 100 x 80 mm. The specimens were given fresh and hardened conblock test and measurement after 28 days after they were made. The research results indicated that cane sugar addition gave insignificant effect to the reduction of cement and water in the mixture because plasticizer material reached cement decrement less than 3%. The compressive strength decreased to 2.5%, 10% and 9% than the normal conblock at the volume ratios of 1:2, 1:4 and 1:6, respectively. Results of compressive strength test showed that samples met the conblock quality standards as referred by SII 0819-83 class I and II. Material cost of conblock m3 with cane sugar addition was 3% cheaper than normal conblock.